2016
DOI: 10.28945/3575
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Electronic Portfolios on Prospective Teachers’ Participation, Motivation, and Autonomous Learning

Abstract: This study explores the impact of electronic portfolios on undergraduate learning in higher education. Based on a descriptive study, it analyses the prospective teacher's perception of use of these tools (electronic portfolio in Moodle-Mahara, in the institutional environment of a university in southern Europe), examining the variables participation, autonomous learning, and motivation. The results show no increase in motivation, but they do show an increase in autonomy, especially a progressive increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Students have the opportunity to review and revise all the tasks that have been done and also discuss them. These results support the results of the D'Angelo & Wright (2012) study which found that the implementation of e-portfolios had a positive effect on students' perceptions of learning, and also could improve the science generic abilities of the student (Ramlawati et al, 2014), increasing participation, motivation and student self-learning ability (Gámiz-Sánchez et al, 2016) and can improve student knowledge sharing (Chang et al, 2018). In addition, these facilities can simultaneously improve student self-regulated learning which includes self-regulated learning processes, intrinsic goal orientation, metacognitive self-regulation, effort regulation, elaboration, rehearsal, and critical thinking (Nguyen & Ikeda, 2015), which of course impact on students' understanding of Cell Biology material.…”
Section: Discussionsupporting
confidence: 87%
“…Students have the opportunity to review and revise all the tasks that have been done and also discuss them. These results support the results of the D'Angelo & Wright (2012) study which found that the implementation of e-portfolios had a positive effect on students' perceptions of learning, and also could improve the science generic abilities of the student (Ramlawati et al, 2014), increasing participation, motivation and student self-learning ability (Gámiz-Sánchez et al, 2016) and can improve student knowledge sharing (Chang et al, 2018). In addition, these facilities can simultaneously improve student self-regulated learning which includes self-regulated learning processes, intrinsic goal orientation, metacognitive self-regulation, effort regulation, elaboration, rehearsal, and critical thinking (Nguyen & Ikeda, 2015), which of course impact on students' understanding of Cell Biology material.…”
Section: Discussionsupporting
confidence: 87%
“…And the result showed there were students reached a very good category. In conclusion, REAP strategy successfully improved students' reading comprehension REAP effect on students' reading comprehension and she found there is a significant difference between the students who are taught by using REAP strategy and the students who are not taught by using REAP strategy and the material that she used in her study was narrative text [17,18].…”
Section: Discussionmentioning
confidence: 83%
“…According to Gámiz-Sánchez, Gallego-Arrufat, and Crisol-Moya [62], teachers' initial training must back methodologies that involve students' active participation, supported by their personal effort and work. Two decades ago, e-portfolios appeared under these premises, which were incorporated in future teachers' training [63][64][65][66][67].…”
Section: E-portfolio As a Tool For Consciousness Trainingmentioning
confidence: 99%
“…The e-portfolio learning model has an individualized nature, where students' experiences depend on their knowledge, preferences, needs, and interests [82]. On the other hand, students are more involved in the construction of the learning process, which increases their awareness and their ability to identify problems, root causes, and potential solutions [62,69]. Therefore, e-portfolios provide a technological context that fosters the development of conscious, committed, and critically active professionals [40,70,84].…”
mentioning
confidence: 99%